Digital marketing support for tape products in Banjarsari Village, Malang Regency - Livia Windiana; Istis Baroh; Anas Tain (Community Empowerment, 2024)
The community service activity aims to provide training and marketing assistance for tape craftsmen in Banjarsari Village, Ngajum District, Malang Regency. The stages of the activity are through preparation, training and assistance, as well as monitoring and evaluation. Training is provided with product marketing materials, namely direct marketing and digital marketing (online). The results of the activity show that the training and assistance carried out are able to open up broader marketing insights and show great digital marketing potential. The target partners are very active and cooperative during the assistance. Tape craftsmen can market their products through the online platform they are interested in. The result is that many products can be ordered online through various platforms, although not yet optimal.